A rare case of malignant chondroid syringoma of scalp - Rajesh Malik; Agamya Saxena; Namita Kamath (Wolters Kluwer Medknow Publications, 2013)
Chondroid syringoma represents the cutaneous counterpart of mixed tumor (pleomorphic adenoma) of salivary glands, therefore it is also termed "mixed tumour of the skin." It is generally accepted that there are both eccrine and apocrine variants of mixed tumors of skin. Malignant chondroid syringoma is a malignant eccrine neoplasm that is very rarely encountered in radio-pathological and clinical practice. Unlike the benign variety which occurs most often on the head and neck, malignant chondroid syringomas are most often found on the trunk and extremities. The usual presentation is that of an asymptomatic slow-growing mass in the region of head or neck. We present here a case report of histopathologically proven malignant chondroid syringoma of scalp in occipital region, with dural invasion. Malignant chondroid syringomas clinically appear as very large nodules and they metastasize at a very high rate. The treatment of these malignancies is surgical excision.